Fuzzy Optimization for Speed Controller of an Indirect Vector Controlled Induction Motor Drive Using Matlab Simulink - Anggun, Anugerah; Omar, Rosli; Sulaiman , Marizan; Ahmad, Azhar (Little Lion Scientific Islamabad Pakistan, 2011)
The aim of this paper is to investigate the performance of a Fuzzy-Logic-Controller (FLC) which is applied on three-phase induction motor drive system for high-performance industrial applications. In this paper, the FLC is used as a speed controller to replace the conventional PI speed controller. The FLC will determine the time of switching on the Space Vector Pulse Width Modulation (SVPWM) inverter that supplies power to drive the induction motor considering variable direct and quadrature axis inductances. The performance of the suggested technique has been simulated and developed using MATLAB/ SIMULINK for dynamic operating condition, such as certain change in command speed, and step change in load. The simulation result shows the feasibility of the proposed technique in order to improve the speed response and low torque ripple on three phase induction motor drive.